CdSe-sensitized branched CdS hierarchical nanostructures for efficient photoelectrochemical solar hydrogen generation. Issue 16 (8th April 2016) - Han, Zonghu; Wang, Meng; Chen, Xiangyan; Shen, Shaohua
Abstract : CdSe-sensitized branched CdS hierarchical nanostructures showed an improved photoelectrochemical performance for solar hydrogen generation as a result of the synergy of improved optical absorption and promoted charge separation. Abstract : A two-step hydrothermal process was used to synthesize branched CdS hierarchical nanostructures, which were then sensitized by CdSe via a chemical bath deposition method. CdS nanorods grew on the surface of the existing CdS nanorods to form hierarchical assemblies. After the chemical bath deposition process, core–shell structures of branched CdS nanorods covered by a uniform CdSe overlayer were formed. The branched hierarchical nanostructure improved the optical absorption by increasing the optical path via additional light trapping, as well as increasing the contact area between the electrode and electrolyte for more reactive sites, contributing to the higher photoelectrochemical performance than that obtained for the rod-like nanostructures. After CdSe sensitization, with the optical absorption greatly extended to longer wavelengths and the photoexcited charge carriers efficiently separated at the type II CdS/CdSe interface, the branched CdS/CdSe hierarchical nanostructures showed considerably increased photoelectrochemical performance compared with the CdS/CdSe nanorods, with a photoconversion efficiency for solar hydrogen generation of 2.7%.